Granulocyte colony‐stimulating factor attenuates liver damage by M2 macrophage polarization and hepatocyte proliferation in alcoholic hepatitis in mice. Issue 9 (23rd August 2022) - Cho, Yeonhee; Joshi, Radhika; Lowe, Patrick; Copeland, Christopher; Ribeiro, Marcelle; Morel, Caroline; Catalano, Donna; Szabo, Gyongyi
Abstract: Massive inflammation and liver failure are main contributors to the high mortality in alcohol‐associated hepatitis (AH). In recent clinical trials, granulocyte colony‐stimulating factor (G‐CSF) therapy improved liver function and survival in patients with AH. However, the mechanisms of G‐CSF‐mediated beneficial effects in AH remain elusive. In this study, we evaluated effects of in vivo G‐CSF administration, using a mouse model of AH. G‐CSF treatment significantly reduced liver damage in alcohol‐fed mice even though it increased the numbers of liver‐infiltrating immune cells, including neutrophils and inflammatory monocytes. Moreover, G‐CSF promoted macrophage polarization toward an M2‐like phenotype and increased hepatocyte proliferation, which was indicated by an increased Ki67‐positive signal colocalized with hepatocyte nuclear factor 4 alpha (HNF‐4α) and cyclin D1 expression in hepatocytes. We found that G‐CSF increased G‐CSF receptor expression and resulted in reduced levels of phosphorylated β‐catenin in hepatocytes. In the presence of an additional pathogen‐associated molecule, lipopolysaccharide (LPS), which is significantly increased in the circulation and liver of patients with AH, the G‐CSF‐induced hepatoprotective effects were abolished in alcohol‐fed mice. We still observed increased Ki67‐positive signals in alcohol‐fed mice following G‐CSF treatment; however, Ki67 and HNF‐4α did not colocalize in LPS‐challenged mice. Conclusion: G‐CSF treatment increases immune cell populations, particularly neutrophil counts, and promotes M2‐like macrophage differentiation in the liver. More importantly, G‐CSF treatment reduces alcohol‐induced liver injury and promotes hepatocyte proliferation in alcohol‐fed mice. These data provide new insights into the understanding of mechanisms mediated by G‐CSF and its therapeutic effects in AH.